The Whack-a-Mole Game: Tobin Taxes and Trading Frenzy - Cai, Jinghan; He, Jibao; Jiang, Wenxi; Xiong, Wei (Review of Financial Studies, 2021)
Abstract To dampen trading frenzy in the stock market, the Chinese government tripled the stamp tax for stock trading on May 30, 2007. The greatly increased trading cost triggered a migration of the trading frenzy from the stock market to the warrant market, which was not subject to the stamp tax. This migration exacerbated a price bubble in the warrant market. Our analysis of investor account data uncovers not only large inflows of new investors to the warrant market but also greatly intensified trading by existing warrant investors. This episode exemplifies the so-called “whack-a-mole” game in financial regulations.